Deskripsi Topik Pembicaraan yang Tidak Menyinggung Privasi Bagi Penutur Bahasa Jepang dan Penutur Bahasa Indonesia - Sanjaya, Sonda; Kusnendar, Muhamad (Universitas Muhammadiyah Yogyakarta, 2018)
This descriptive quantitative study aims at finding out conversational topics being talked about by Japanese and Indonesian speakers when they meet people for the first time. Additionally, this study also explores conversational topics among Japanese speakers, which are considered as non-private by Indonesian speakers. Furthermore, the conversational topics among Indonesian speakers, which are considered as non-private by Japanese speakers, were also investigated. To collect the data, survey technique was employed. 93 Japanese speakers and 101 Indonesian speakers voluntarily took part in this study. The data analysis revealed that the conversational topics among Japanese speakers, which have ever been talked about in their first contact included name, hobby, hometown, weather, vacation, workplace, current issues, family, social media accounts, birthday, re-lationship status, email address, address, mobile phone number, children, marital status, employment status, salary, as well as the content of their wallet, bedroom, mobile phone and computer. Meanwhile, the conversational topics among Indonesian speakers, which have ever been talked about in their first contact included name, workplace, hometown, address, hobby, employement status, family, current issues, mobile phone number, social media accounts, children, vacation, marital status, weather, and email address. In addi-tion, conversational topics among Japanese speakers, which are considered as non-pri-vate by Indonesian speakers included name, hobby, hometown, weather, vacation, work-place, current issues, family, social media accounts, birthday, email account, address, mobile phone number, children, and employment status. The conversational topics among Indonesian speakers, which are considered as non-private by Japanese speakers included name, workplace, hometown, hobby, family, current issues, children, vacation and weather.Â Â